Metadata Schema to Facilitate Linked Data for 3D Digital Models of Cultural Heritage Collections: A University of South Florida Libraries Case Study. Issue 2 (17th February 2018) - Mi, Xiying; Pollock, Bonita M.
ABSTRACT: The University of South Florida Libraries house and provide access to a collection of cultural heritage and 3D digital models. In an effort to provide greater access to these collections, a linked data project has been implemented. A metadata schema for the 3D cultural heritage objects which uses linked data is an excellent way to share these collections with other repositories, thus gaining global exposure and access to these valuable resources. This article will share the process of building the 3D cultural heritage metadata model as well as an assessment of the model and recommendations for future linked data projects.